1970
DOI: 10.1254/jjp.20.536
|View full text |Cite
|
Sign up to set email alerts
|

A Release of Renin From Dog Kidney Cortex Slices

Abstract: A release of renin from kidney cortex slices in vitro was first reported by the present authors (1). Recently, the renin release from kidney slices of rats, pretreated with de oxycorticosterone acetate, clipping of renal artery, bleeding or decapitation, was shown by Jong (2) ' and BoCovic et al. (3). In their experiments, the fundamental process of renin release has not been made clear. In our previous paper, it was pointed out that renin is released from dog kidney slices into an incubation medium depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1972
1972
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…This stimulatory effect resembles the classic effect of calcium in secretory cells in which elevations of calcium initiate, facilitate or maintain exocytotic processes [27]. In fact there are also a few reports on a stimulatory effect of calcium or calcium ionophores on renin secretion [13,17,24,26]. It could be speculated, in the light of our results, that in those instances the stimulatory effect of calcium may have overridden an inhibitory effect of calcium on renin secretion.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This stimulatory effect resembles the classic effect of calcium in secretory cells in which elevations of calcium initiate, facilitate or maintain exocytotic processes [27]. In fact there are also a few reports on a stimulatory effect of calcium or calcium ionophores on renin secretion [13,17,24,26]. It could be speculated, in the light of our results, that in those instances the stimulatory effect of calcium may have overridden an inhibitory effect of calcium on renin secretion.…”
Section: Discussionsupporting
confidence: 73%
“…Unlike other enCorrespondence to: A. Kurtz docrine and exocrine cells, in which a rise of calcium initiates, facilitates, or maintains secretory activity [27], an increase in [Ca]~ is thought to inhibit secretion from JG cells, a phenomenon that is referred to as the "calcium paradox" [14]. This indirect evidence results from observations that renin secretion is (a) inhibited by calcium-mobilizing hormones [34,35], (b) inversely related to the extracellular calcium concentration [10,12,15,18,19,26], (c) inhibited by manoeuvres that are thought either to enhance calcium entry or to inhibit calcium extrusion [4-6, 9, 25, 28], and (d) enhanced by manoeuvres thought either to inhibit intracellular calcium release or calcium influx [i, 2,6]. It is an open question whether calcium has a unique directly inhibitory effect on exocytosis of secretory granules in JG cells or has, rather as it has in other secretory cells, a fusogenic effect that is overriden by a secondary calcium-dependent effect, which in turn acts inhibitorily in JG cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 7th hospital week, a calcium infusion test was performed in the morning after an overnight fast. Calcium was infused as calcium (Morimoto et al, 1970;Michelakis, 1971;Chen and Poisner, 1976). However, calcium infusion performed when the patient became normocalcemic, normoreninemic and normotensive did not increase PRA in spite of an increase in serum calcium.…”
Section: Methodsmentioning
confidence: 99%
“…Renin release studies using renal cortical slices have been reported in the rat, rabbit, dog, pig, and recently in the mouse of examine the direct stimuli on juxtaglomerullar cells not mediated by systemic effects. However, the evaluations of some of the essential characters of the experimental system, e.g., energy dependency (1, 2), Ca dependency (2-4), and oxygen demand (5,6) of renin secretion show discrepancies in some of the studies. Me thodological problems seems to be involved in some of the inconsistencies in the experi mental results.…”
mentioning
confidence: 99%